CASE REPORTSA fatal case of descending necrotizing mediastinitis as a complication of odontogenic infection. A case report - Lewandowski, Bogumił; Pakla, Paweł; Wołek, Wojciech; Jednakiewicz, Mariusz; Nicpoń, Jakub (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
This paper presents the case of a 26-year-old female patient in whom descending necrotizing mediastinitis (DNM) developed as a complication of an odontogenic purulent infection of the mouth. Despite the efforts of a multidisciplinary treatment team, the patient died with symptoms of septic shock and multiple organ failure. According to the literature, and as confirmed by our own observations, successful treatment requires early tomographic diagnosis, radical surgery, combination antibiotic therapy, and intensive care.